Successful rituximab treatment of granulomatous/lymphocytic interstitial lung disease in common variable immunodeficiency - Králíčková, P; Kubcová, Š; Kočová, E; Bartoš, V; Souček, O; Rozsíval, P; Vaníček, H; Krčmová, I; Ravčuková, B; Grombiříková, H; Freiberger, T (Epidemiologie, mikrobiologie, imunologie, 2018)
Successful rituximab treatment of granulomatous/lymphocytic interstitial lung disease in common variable immunodeficiency Common variable immunodeficiency, a heterogeneous group of diseases, represents a clinically relevant form of antibody immunodeficiency. Granulomatous/lymphocytic interstitial lung disease is among the most serious complications. A case report is presented of a young women with granulomatous/lymphocytic interstitial lung disease and splenomegaly accompanied by pancytopenia. Intravenous rituximab treatment in monotherapy (at a weekly dose of 375 mg/m2 for four consecutive weeks, repeated six months later) not only led to a significant improvement in clinical symptoms but also to positive morphological and functional lung changes, mitigation of pancytopenia, considerable reduction of alkaline phosphatase level, and disappearance of splenic granulomas. The treatment was well tolerated without any side effects. The case report presented suggests possible efficacy and safety of rituximab monotherapy in patients with a complicated form of common variable immunodeficiency. KEYWORDS Rituximab - antibody immunodeficiency - lung disease - treatment Epidemiol. Mikrobiol. Imunol., 67, 2018, č. 3, s. 142-148.
Keywords: běžná variabilní imunodeficience; Rituximab - antibody immunodeficiency - lung disease - treatment Epidemiol. Mikrobiol. Imunol.; Common Variable Immunodeficiency; 2018; výsledek terapie; Immunologic Factors; Lung Diseases, Interstitial; imunologické faktory; intersticiální plicní nemoci; Rituximab; ženské pohlaví; Humans; s. 142-148; rituximab; č. 3; Female; Treatment Outcome; 67; lidé